0
$\begingroup$

Hi I'm trying to solve the problem when studying for an upcoming test. The given solution is $$y[n]= \frac{1}{b-a}(b^{n+1}-a^{n+1}) \quad \text{for } n\ge0 \ .$$ However, I'm not sure how to reach this point. We have to also verify using the z-transform. Any help would be appreciated so much.

$\endgroup$
3
$\begingroup$

Just do it the hard way by writing out the individual formulas for the general convolution sum \begin{align} y[n] &= \sum_{k=-\infty}^\infty a[k]b[n-k]\\ &= \sum_{k=0}^\infty a[k]b[n-k] &\scriptstyle{\text{because }a[k]=0~\text{whenever } k < 0,}\\ &= \sum_{k=0}^n a[k]b[n-k] &\scriptstyle{\text{because }b[n-k]=0~\text{whenever } k > n,} \end{align} which gives \begin{array}{rclcl} y[0] &= &a[0]b[0] &= &1\\ &&&= &\displaystyle\frac{b^1-a^1}{b-a}\\ y[1] &= &a[0]b[1] + a[1]b[0] &= &b+a\\ &&&= &\displaystyle\frac{b^2-a^2}{b-a}\\ y[2] &= &a[0]b[2] + a[1]b[1] + a[2]b[0] &= &b^2 + ba +a^2\ &&&= &\displaystyle\frac{b^3-a^3}{b-a}\\ &&&= &\displaystyle\frac{b^3-a^3}{b-a}\\ \vdots &= &\ddots~~~\scriptstyle{\text{Hey, Ma! I think I see a pattern developing here}}\\ \\ y[n] &= &a[0]b[n] + a[1]b[n-1] + \cdots + a[n]b[0] &= &b^n + b^{n-1}a + \cdots + ba^{n-1} + a^n\\ &&&= &\displaystyle\frac{b^{n+1}-a^{n+1}}{b-a} \end{array} if you can recall the formula for the sum of a geometric series.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.